Traffic Flows Model of Postal Items Based on Input-output Demands in the Public Postal Network: Case Study of Croatia - Tabak, Pero; Kljak, Tomislav (Promet - Traffic&Transportation, 2012)
This paper presents the method for developing matrix model of postal traffic flows (ordinary communication items) in public postal network according to volume and different end-to-end (E2E) processes, which can be used for selecting of relevant model for accessing the public postal network. The presented traffic matrix model can be adjusted after the measurement of real volumes and selecting the numbers of different E2E processes (according to geographical input-output request). During the simulation of the model it could be possible to detect the optimal solution for accessing the public postal network.KEY WORDS: traffic modelling, postal services, access to the public postal network